EFFECT OF SOME NEW HERBICIDES ON THE COMPETITION ABILITY TO SEVEN MAIZE CULTIVARS ( Zea mays L. ) ON THE WEED ACCOMPANYING - & Shati, Al-khazali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field trials was conducted at Abu-Ghraib Research Station / Agricultural Research Office (33°19ʹ27ʺ.1 North, 44°14ʹ13ʺ.1 East) during spring & fall seasons  of 2014, to study the response of  maize  cultivars (Al-Maha, Baghdad 3, Buhuth 106, Fajer1, Talar, Sara and 5018( to weeds control under different herbicides (2000 cm3.h-1 Guradian , 60 gm.h-1 Arrow, 2000 cm3.h-1 Proponit, 600 cm3.h-1 Crew , Weedy and Weed Free). The experiment was accomplished using randomized complete block design (RCBD) according to  split plot arrangement with three replicates. The study involved six different weed treatments as main treatments, whereas, sub plots comprised of seven maize cultivars. The results revealed a clear effect of different weeds control treatments   most of the studied traits. The treatment  (2000 cm3.h-1 Guradian) gave less mean of weed density reached  9.19 & 14.05 plant.m²  during both seasons   in comparison with  weedy  treatment gave the highest mean of weed density reached 20.81 & 28.81 plant.m² for both seasons respectively. So, the Guradian treatment achieved the highest percentage of weed control which were  55.70 & 50.72 % for both seasons respectively in comparison with  weedy  treatment. And therefore decreased weed dry matter weight where the Guradian treatment gave lowest weed dry matter weight 116.37 & 153.35 gm.m-2 for both seasons respectively. Whereas, the highest weed dry matter weight was in weedy treatment 391.56 & 858.59 gm.m-2 during the both seasons,  and then elevating inhibition percentage 70.35  & 81.34% for both seasons respectively as compared with weedy treatment. Fajer1in the spring season record  the lowest average density reached 8.94 plant.m-2, While Baghdad 3 gave the highest average for this Character reached 11.78 plant.m-2, and In the fall season, Buhuth 106 record  lowest average  to this Character reached 13.72 plant.m-2 while Sarah gave the highest average for this Character reached 16.22 plant.m-2. Most of maize cultivars showed a response to the different treatments of weed control. Where, The Guradian treatment with Al-Maha  gave less mean of weed density reached 7.33 plant.m²  in comparison with  weedy  treatment with Baghdad3 gave the highest mean of weed density reached 25.33 plant.m²during the spring season. While, in the fall season; The Guradian treatment with Buhuth 106 gave less mean of weed density reached 12.00  plant.m²  in comparison with  weedy  treatment with Sara gave the highest mean of weed density reached 34.33 plant.m²during the spring season. finally, We can conclude that all Herbicides  have reduced the  weed density  and decreased weed dry matter weight  in varying proportions depending on the nature of the chemical composition of the herbicide treatment compared with weedy treatment and also  the maize cultivars showed  ability to compete with the weed and thus Difference  at ratios of reducing the weed density and weed  dry matter weights.